Customers’ perception on the adoption of Islamic green banking in Malaysia - 'Ayna, Abdul Wahab (2021)
Before our next generations wear the green willow, we should go green and protect our Earth. Banks are the major factor in protecting the nature by performing the concept of Green Banking that involves in developing bank strategies that focus on essential economic development and environmental-friendly measures. This study attempts to review the precept of Islamic green banking adoption in Malaysia by considering the view of customers through their perception and demographic factors. This study also implicated that, there is a high positive awareness of the respondents about Islamic green banking so the Islamic bank institutional should raise their awareness of green activities and this study can help the Islamic banks to analyse their customers perception through their demographic factors. Through a quantitative research by using 384 respondents of Islamic banks’ customers in Malaysia including all four regions, it is found that for each demographic factors which are age, gender, religion, race and education, those who are 20-29 years old, female, Muslim, Malay with a bachelor degree holder more likely to adopt the Islamic green banking because they make up the majority of the respondents. This research has been the first to find out which group in the demographic characteristics are more likely to adopt Islamic green banking. However, there should be more research related to this study that identify the demographic factors that can affect the customers perception on the adoption of Islamic green banking.